2014
DOI: 10.1093/hmg/ddu485
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of hRNase H2 activity in Aicardi–Goutières syndrome cells leads to replication stress and genome instability

Abstract: Aicardi–Goutières syndrome (AGS) is an inflammatory encephalopathy caused by defective nucleic acids metabolism. Over 50% of AGS mutations affect RNase H2 the only enzyme able to remove single ribonucleotidemonophosphates (rNMPs) embedded in DNA. Ribonucleotide triphosphates (rNTPs) are incorporated into genomic DNA with relatively high frequency during normal replication making DNA more susceptible to strand breakage and mutations. Here we demonstrate that human cells depleted of RNase H2 show impaired cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 55 publications
10
65
0
Order By: Relevance
“…Consistent with these data from mice, ribo nucleotides have been shown to accumulate in the DNA of cells from patients with AGS who have mutations in RNASEH2A and RNASEH2B. Cells from these patients also have impaired cell cycle progression, and this is associated with chronic activation of post-replication repair mechanisms [47][48][49] . Furthermore, depletion of SAMHD1 in fibroblasts was reported to result in features of increased genomic DNA damage 50 .…”
Section: Retroelements and Dna Damage In Agssupporting
confidence: 58%
“…Consistent with these data from mice, ribo nucleotides have been shown to accumulate in the DNA of cells from patients with AGS who have mutations in RNASEH2A and RNASEH2B. Cells from these patients also have impaired cell cycle progression, and this is associated with chronic activation of post-replication repair mechanisms [47][48][49] . Furthermore, depletion of SAMHD1 in fibroblasts was reported to result in features of increased genomic DNA damage 50 .…”
Section: Retroelements and Dna Damage In Agssupporting
confidence: 58%
“…The RNase H2-mediated ribonucleotide excision repair system is thought to be the primary mechanism for removing rNMPs from DNA in both prokaryotes and eukaryotes (5). The importance of this repair system in mammals is demonstrated by the fact that RNase H2 is essential for embryonic development in mice (4,10) and by the observation that mutations in the RNase H2 gene are seen in human patients with the autoimmune inflammatory disorder Aicardi-Goutières syndrome (6,11,12). Characterizing the cellular pathways that recognize and remove rNMPs from DNA therefore has the potential to provide a better understanding of a number of human pathologies and disease processes, including autoimmune disorders such as Aicardi-Goutières syndrome and lupus and also carcinogenesis and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from a variety of model eukaryotic systems, including yeast (7)(8)(9), mice (4,10), and Aicardi-Goutières syndrome patient-derived cells (11,12), have shown that the disruption of RNase H2 results in an accumulation ribonucleotides in genomic DNA. The presence of ribonucleotides in DNA is problematic for cellular and organismal function, as evidenced by the replication stress, mutagenesis, genomic instability, and developmental defects that are observed in these experimental systems upon disruption of RNase H2 function.…”
mentioning
confidence: 99%
“…Under normal conditions, the cell can use the transient presence of these polymerases to its advantage: ribonucleotide incorporation by polymerase mu (Pol-µ) is thought to be beneficial for double-strand break repair by nonhomologous end joining 7,16 , whereas ribonucleotide incorporation on the leading strand by Pol-ε promotes mismatch repair 17,18 . However, failure to remove embedded ribonucleotides, i.e., the absence of RNase H2, results in genome instability 6,8,[19][20][21][22][23][24][25] . This may be linked to heritable autoinflammatory disorders such as Aicardi-Goutières syndrome 21,[25][26][27] and systemic lupus erythematosus 21 , and it could have relevance for the neurodegenerative disorder ataxia with oculomotor apraxia 1 (refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, failure to remove embedded ribonucleotides, i.e., the absence of RNase H2, results in genome instability 6,8,[19][20][21][22][23][24][25] . This may be linked to heritable autoinflammatory disorders such as Aicardi-Goutières syndrome 21,[25][26][27] and systemic lupus erythematosus 21 , and it could have relevance for the neurodegenerative disorder ataxia with oculomotor apraxia 1 (refs. 28,29).…”
Section: Introductionmentioning
confidence: 99%